A voice for freedom - Sahgal, Nayantara, 1927- (Hind Pocket Books, 1977)
Polemic against the repressive actions of Indira Gandhi, b. 1917, former Prime Minister of India, during emergency, 1975-1977; articles speeches and interviews.